Green Innovation Implementation: A Systematic Review and Research Directions - Qin, Xiangru; Muskat, Birgit; Ambrosini, Véronique; Mair, Judith; Chih, Ying-Yi (Journal of Management, 2026)
Green innovation is an organizational strategy aimed to address climate crises and create low-carbon growth, yet, its implementation remains a significant challenge. We focus on green innovation implementation (GII) and argue that GII is a distinctive strategic process. Traditional innovation implementation, centered on short-term economic growth, can be problematic as it often decouples nature from innovation in the pursuit of profit maximization. Thus, the traditional approach fails to adequately explain GII, specifically, who implements it and how they do it. We adopt a strategy-as-practice perspective and conduct a systematic review of 224 journal articles across various management fields to synthesize existing knowledge of GII. This review makes three main contributions. First, we posit that GII is theoretically distinct with unique implementation challenges: recoupling nature with innovation implementation introduces complex antecedents and environment-inclusive benefits, requiring a long-term implementation process and a broader scope. Second, we develop a framework that synthesizes practitioners, antecedents, processes, and impact of GII from three theoretical foci: (1) resource-based perspective, (2) sustainable value-driven perspective, and (3) institutional perspective. This framework complements the traditional understanding of innovation implementation by offering diverse theoretical insights on GII. Third, we propose theoretical and methodological directions for future research to advance knowledge on green innovation and provide meaningful insights on GII.